Oculo-Visceral Reflexes Revisited: A Comprehensive Review - Ashok Kumar Khurana; Aruj Kumar Khurana; Bhawna P. Khurana; Indu Bala Khurana (Delhi Journal of Ophthalmology)
Oculovisceral reflexes, in addition to oculocardiac reflex (OCR), include oculorespiratory reflex (ORR), oculodepressor reflex (ODR), oculogastric reflex (OGR), and the other needing unveiling. The OCR is a well-recognized phenomenon with potentially significant clinical implications. It is essential for health-care providers, particularly those involved in eye surgeries, i.e., eye surgeons and anesthetists to be knowledgeable about the OCR and take appropriate measures to prevent and manage its effects to ensure patient safety. While our understanding of the ORR has advanced in recent years, many questions remain unanswered. We urge the ophthalmology community to revisit this intriguing connection and encourage further research in this area. The ODR and OGR are the least studied. Ocular surgery involving manipulation of extraocular muscles such as squint, enucleation, and retinal detachment is very frequently performed. Further, ophthalmologists need to be aware of OCR in cases of entrapment of muscles in orbital floor fracture. Therefore, prevention of OCR, ORR, and ODR becomes imperative in all such cases. Since the retrobulbar injection of 2% xylocaine blocks the afferent pathway of all the three reflexes, its use has been recommended even when the surgery is performed under general anesthesia. In addition, intravenous atropine or glycopyrronium should also be used to block the efferent pathway of OCR and other visceral reflexes. Further, controlled ventilation must be preferred over spontaneous breathing, at least immediately before, after, and during muscle traction.